Empowering Local Tourism Stakeholders: A Muslim-Friendly Approach to Sustainable Geo-Tourism in Langkawi’s UGGp - Siti Syahirah Saffinee; Mohammad Aizat Jamaludin (HH PUBLISHER, 2024)
Non-Indexed Publication